A light-scattering study of the scattering matrix elements of Arizona Road Dust. (September 2015) - Wang, Yuli; Chakrabarti, Amitabha; Sorensen, Christopher M.
Abstract: We report measurements of the light scattering matrix elements of Arizona Road Dust, which has irregular shapes. Our experimental apparatus used photodiode arrays to detect scattered light simultaneously at many angles including small angles that are necessary for accurate characterization of large particles. The setup was calibrated with single slit diffraction and water droplet scattering. Guinier analysis yielded the dust particle size. Q-space analysis of the dust scattering yielded a comprehensive description of scattering in terms of power laws with quantifiable exponents. Highlights: The scattering apparatus detects light at 31 angles, 0.3–157°, simultaneously. Three sizes of Arizona Road Dust are studied. Guinier analysis characterizes the radii of gyration of the dusts. Q-space analysis of dust scattered intensity reveals power laws with exponents.